Incidence and Pathological Analysis of Parasitic Infections in Underserved Communities - Abhishek Raval; Manan Jadav; Ritesh Gohil; Maulik Vora (Journal of Pharmacy and Bioallied Sciences)
Background: Parasitic infections remain a significant public health concern, particularly in underserved communities where access to healthcare and sanitation is limited. This study aims to investigate the incidence and pathological characteristics of parasitic infections in such communities, providing insights into the prevalence and impact of these infections on public health. Materials and Methods: A cross-sectional study was conducted in underserved communities over a period of one year. A total of 500 participants were randomly selected and screened for parasitic infections through stool and blood samples. The samples were analyzed using microscopy and polymerase chain reaction (PCR) techniques to identify and quantify parasitic species. Pathological examinations were performed to assess the impact of infections on host tissues. Results: The incidence of parasitic infections was found to be 35% among the study population. The most common parasites identified were Ascaris lumbricoides (40%), Giardia lamblia (25%), and Entamoeba histolytica (20%). Pathological analysis revealed that Ascaris lumbricoides caused significant intestinal inflammation in 30% of infected individuals, while Giardia lamblia was associated with malabsorption syndrome in 15% of cases. Entamoeba histolytica was linked to liver abscesses in 10% of the infected participants. Conclusion: Parasitic infections are highly prevalent in underserved communities, with significant pathological impacts on affected individuals.